(3GdMOGFbs - (3GdOQGRj GdHMQGf, GHf YUahQ, jhSa Hf CMeO Hf EHQGgje, J(B1186(3g`s ((3MSjf Hf Ydj GdcYHjs)
(3ChdgG (B:s
(3HSe Gddg (B.. (3agQSJ (B.. (3GdMeO ddg QH GdYGdejf (B.. (3cJGH GdRcGI hgj dZI JWdb Ydi eYfjjf GdWgGQI hGdRjGOI hGdfeh hef GdChd bhdg YR hLd bO CadM ef RcGgG Cj WgQgG ef GdCNdGb GdOfjI hef GdKGfj bhdg YR hLd (B" (3Pdc CRci dce hCWgQ (B" ..s
(3BNQgG (B:s
.. (3hdG jecf GdGJjGf HeKd gPG GdUhe EdG HeKd gjFJg hgh gjFI GdGYJcGa acGf GdGYJcGa hGLHG GfJgi , aEfg eJi KHJ HCf GdUhe ZjQ hGLH ddGYJcGa ceG CTQfG Edjg adG hLg dgPG GdcdGe hHGdLedI aGdhLg Cf jbGd Cf GdMce (B...(3gPG GdcdGe aj GdLRA GdQGHY (B.. (3hjJdhg cJGH GdML(B.s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B8/215s
(3GdPQjYI (B6/1557s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis